2018
DOI: 10.1080/00224499.2018.1475546
|View full text |Cite
|
Sign up to set email alerts
|

Loving Oneself: The Associations Among Sexually Explicit Media, Body Image, and Perceived Realism

Abstract: Online sexually explicit material (SEM) is a popular media source, but little is known about its association with body image. This study explored whether perceived realism of SEM mediated the direct association of SEM use on body image while accounting for gender differences. Young adults (N = 393; ages 19 to 30; 53.4% women) recruited through a crowdsourcing Web site completed an anonymous online survey that assessed SEM use, perceptions of the realism of SEM, and body image. Body satisfaction, genital self-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…While several studies have confirmed the negative relationship between the use of sexually explicit material and different aspects of body satisfaction (Peter & Valkenburg, 2014;Tylka, 2015), one study reported that the relationship between the use of sexually explicit material and a better body image was fully mediated by perceived realism of sexually explicit material (Vogels, 2018). However, only as few as three studies have quantitatively assessed the relationship between the exposure/use of sexually explicit material and body surveillance/monitoring in samples of adolescent and young adult men.…”
Section: Objectification Theory and Sexually Explicit Materialsmentioning
confidence: 99%
“…While several studies have confirmed the negative relationship between the use of sexually explicit material and different aspects of body satisfaction (Peter & Valkenburg, 2014;Tylka, 2015), one study reported that the relationship between the use of sexually explicit material and a better body image was fully mediated by perceived realism of sexually explicit material (Vogels, 2018). However, only as few as three studies have quantitatively assessed the relationship between the exposure/use of sexually explicit material and body surveillance/monitoring in samples of adolescent and young adult men.…”
Section: Objectification Theory and Sexually Explicit Materialsmentioning
confidence: 99%
“…They are noteworthy because they appeared to be founded on a set of items that have been the focus of some validation efforts, but in each case, adaptations were made without clear justification. All six of these studies (Peter & Valkenburg, 2009, 2011bVandenbosch & van Oosten, 2017;van Oosten, 2016;Vogels, 2018;Vogels & O'Sullivan, 2019), for example, used only four of the original five items proposed by Peter and Valkenburg (2006), with no mention of why the fifth item (i.e., the use of "erotic contact sites", p. 186), with which the scale validity was originally supported, was excluded. Further, the original scale asked about pornography use over the past six months, but three of these studies used either a two month or a four month assessment window.…”
mentioning
confidence: 99%
“…The studies included a total of 29,881 participants. Seven studies included only females (Davis et al, 2019; Dogan and Yassa, 2019; Laemmle-Ruff et al, 2019; Sharp et al, 2016; Truong et al, 2017; Tylka and Calogero, 2019; Tylka and Kroon Van Diest, 2014), 11 only included males (Duggan and McCreary, 2004; Griffiths et al, 2018; Kvalem et al, 2016; Leickly et al, 2017; Morrison et al, 2007; O’Brien et al, 2015; Prokop, 2016; Sevic et al, 2020; Sharp and Oates, 2019; Tylka, 2015; Whitfield et al, 2018), and the remaining eight contained mixed gender samples (Albright, 2008; Cranney, 2015; Dawson et al, 2020; Doornwaard et al, 2014; Goldsmith et al, 2017; Mattebo et al, 2012; Peter and Valkenburg, 2014; Vogels, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents were the target population in four studies (Doornwaard et al, 2014; Sevic et al, 2020; O’Brien et al, 2015; Mattebo et al, 2012), young adults or college students were included in seven studies (Davis et al, 2019; Dawson et al, 2020; Goldsmith et al, 2017; Prokop, 2016; Tylka, 2015; Tylka and Kroon Van Diest, 2014; Vogels, 2019), and adults were studied in 14 studies (Albright, 2008; Cranney, 2015; Dogan and Yassa, 2019; Duggan and McCreary, 2004; Griffiths et al, 2018; Kvalem et al, 2016; Laemmle-Ruff et al, 2019; Leickly et al, 2017; Morrison et al, 2007; Sharp et al, 2016; Sharp and Oates, 2019; Truong et al, 2017; Tylka and Calogero, 2019; Whitfield et al, 2018). One study included adolescents, young adults, and adults (Peter and Valkenburg, 2014).…”
Section: Resultsmentioning
confidence: 99%